ANALISIS FAKTOR-FAKTOR KEUANGAN YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Mangundap, Rima D.; Karamoy, Herman; Alexander, Stanly (Universitas Sam Ratulangi, 2013)
Companies as a form of organization in general has a specific goal to be achieved in an effort to meet the interests of its members. Success in achieving the company's goal is performance management. Performance appraisal or performance of a company is measured because it can be used as the basis for decision making both internally and eksternal.Tujuan of this study was to determine Is asset structure, debt ratios, and capital structure affect the financial performance of companies either simultaneously or partially. The method used in this study is the linear regression equation berganda.Dalam simultaneous testing result that financial factors have a significant influence on the financial performance of the company. This is evidenced by calculated F value is greater than the value of F table Â and significant values significantly smaller than the size. Subsequently the partial test of the three variables tested only a capital structure that has a significant influence on the financial performance of the company.